Recessive mutations in the cancer gene Ataxia Telangiectasia Mutated (ATM), at a locus previously associated with metformin response, cause dysglycaemia and insulin resistance. Issue 3 (24th December 2015) - Connelly, P. J.; Smith, N.; Chadwick, R.; Exley, A. R.; Shneerson, J. M.; Pearson, E. R.
Abstract: Aim: To investigate glucose and insulin metabolism in participants with ataxia telangiectasia in the absence of a diagnosis of diabetes. Methods: A standard oral glucose tolerance test was performed in participants with ataxia telangiectasia ( n = 10) and in a control cohort ( n = 10). Serial glucose and insulin measurements were taken to permit cohort comparisons of glucose‐insulin homeostasis and indices of insulin secretion and sensitivity. Results: During the oral glucose tolerance test, the 2‐h glucose (6.75 vs 4.93 mmol/l; P = 0.029), insulin concentrations (285.6 vs 148.5 pmol/l; P = 0.043), incremental area under the curve for glucose (314 vs 161 mmol/l/min; P = 0.036) and incremental area under the curve for insulin (37, 720 vs 18, 080 pmol/l/min; P = 0.03) were higher in participants with ataxia telangiectasia than in the controls. There were no significant differences between groups in fasting glucose, insulin concentrations or insulinogenic index measurement (0.94 vs 0.95; P = 0.95). The Matsuda index, reflecting whole‐body insulin sensitivity, was lower in participants with ataxia telangiectasia (5.96 vs 11.03; P = 0.019) than in control subjects. Conclusions: Mutations in Ataxia Telangiectasia Mutated (ATM) that cause ataxia telangiectasia are associated with elevated glycaemia and low insulin sensitivity in participants without diabetes. This indicates a role of ATM in glucose and insulin metabolic pathways. What's new?: In a genome‐wide association study in 2011, our group identified Ataxia Telangiectasia Mutated (ATM ) as a potential candidate gene associated with glycaemic response to metformin. In this study, we investigate the role of ATM in carbohydrate metabolism by performing an oral glucose tolerance test in participants with recessive mutations in this gene, causing the condition ataxia telangiectasia, and healthy control subjects. We show that ataxia telangiectasia is associated with elevated glycaemia and decreased insulin sensitivity. These results indicate a significant role of ATM in glucose and insulin metabolic pathways.